THERMAL CONDUCTIVITY OF PARTITION BOARD BY POLYMER COMPOSITE WITH FILLER EMPTY FRIUT BUNCHES FIBRES - Batumahadi Siregar; Banu Nursanni; Sapitri Januariyansah; Sutrisno Sutrisno; Kinanti Wijaya (Jurnal Rekayasa Mesin, 2023)
Utilization and management of Empty Fruit Bunches (EFB) fibre continue to develop as the main ingredient and additional material used in various industrial products. The technological breakthrough targeted in this study is the developed EFB fibre as a filler in polymer composite partition boards which are used as heat retainers in the interior construction of buildings. The partition board is a heat insulator, and its thermal conductivity is affected by mass density and porosity. The purpose of this study was to determine the heat resistance of partition board products to reduce the heat entering the room from outside by propagating through walls exposed to direct sunlight. The test method used is adopted from ASTM C177-13, namely the measurement of heat propagation with a modification of the heat source of 40 watts. In addition, mass density tests (referring to SNI 03-2105-2006) and water absorption (referring to ASTM D5229M-12) were also carried out on the product. The specimens were based on the formation of Singapore Highpolymer Chemical Product (SHCP) 2667 WNC polyester resin matrix partition board with weight fractions of 25%, 30%, and 35% chop strand mat (CSM). The test results show that the highest thermal conductivity value is found on the board with a weight fraction of 25%, namely 0.153 W/m.Â°C with a mass density of 1.16 g/cm3 and a water absorption capacity of 3.38%. However, the lowest thermal conductivity value was found in the fibre with weight fraction of 35%, namely 0.147 W/m. Â°C at a mass density of 1.24 g/cm3 and a water absorption capacity of 3.75%.